Case report: The impact of dissociated response of immunotherapy on the treatment strategy of advanced head and neck cancer - Jiang, Siqing; Li, Xin; Li, Jin (Frontiers in Immunology, 2024)
Some special therapeutic responses may appear during immunotherapy, such as hyperprogression, pseudoprogression and so on. Dissociated response of immunotherapy has been clinically reported in recent years mainly in lung cancer and kidney cancer. Since there were poor prognosis and simple treatment of advanced head and neck cancer, the application of immunotherapy in head and neck cancer has risen in recent years.But the dissociated response of immunotherapy in head and neck cancer is rarely reported. We reported two series of cases of advanced head and neck cancer that showed dissociated response after immunotherapy, tumor progression was assessed by imaging methods such as PET-CT ， enhanced CT and enhanced MR, and reviewed the literature related to dissociated response in immunotherapy. We propose that the dissociated response of immunotherapy may affect the treatment strategy of advanced head and neck cancer, but more clinical analys es and researches are needed to confirm it.The dissociated response to immunotherapy may profoundly influence the decision -making of local and systemic therapy for advanced head and neck cancer with distant metastasis.